Laser polarization-variable autofluorescence of the network of optically anisotropic biological tissues: Diagnostics and differentiation of early stages of cancer of cervix uteri - Yu. A. Ushenko; M. I. Sidor; N. Pashkovskaia; G. D. Koval; Yu. F. Marchuk; D. Andreichuk (Journal of Innovative Optical Health Sciences, 2014)
This research presents the results of investigation of laser polarization fluorescence of biological layers (histological sections, cytological smears) in the task of diagnostics and differentiation of early stages of cancer: Dysplasia — cervical microinvasive carcinoma of cervix uteri. The analytical conditions of polarization-optimal probing of biological layers were determined basing on the model of linear birefringence and dichroism of birefringent (fibrillar, porphyrin) networks. The technique of polarization-variable laser autofluorescence was developed and experimentally tested. The objective criteria (statistical moments) of differentiation of histological sections autofluorescent images of endometrium biopsy and cytological smears of it mucous coat were defined. The operational characteristics (sensitivity, specificity, accuracy) of this technique were determined concerning the positions of probative medicine, and clinical efficiency.